Influence of orthodontic treatment with functional appliances on pharyngeal dimensions in patients with Class II malocclusions – review of literature - Paluch, Zbigniew; Twardokęs, Marta; Stelmańska, Karolina; Cielińska, Monika (Journal of Stomatology, 2015)
Introduction. Maxillary and/or mandibular position and dimension, which are parts of the facial skeleton, may be related to the dimensions of the particular parts of the pharynx. The use of functional appliances in the treatment of children with Class II malocclusions before and during the growth period is a widely applied method of orthodontic treatment. Despite the fact that these appliances mainly affect the dentoalveolar part, the changes in other skeletal structures and in upper airways have also been reported. Aim of the study. To identify changes in upper airway dimensions as a result of treatment with functional appliances in patients with Class II malocclusions without respiratory disturbances. Material and methods. The MEDLINE medical database was searched by entering the keywords: pharynx and orthodontic appliances. In order to find the non-indexed papers in the MEDLINE database, the references of the accepted articles were additionally verified. The articles included in the present review were written in English and were related to the studies on patients with Class II malocclusions before or during the growth period. The subjects were treated with functional appliances. The morphometric measurements on LCRs were also present. The articles excluded from the review were related to subjects who underwent surgical procedures within the neck and the head, subjects with cleft lip and palate or pathology within the upper airways (UAs). Results. Twelve articles were obtained after the analysis of the search results. Summary. Statistically significant changes were observed in the values of the selected pharyngeal dimensions after the use of particular functional appliances for the treatment of Class II malocclusions.